2010
DOI: 10.58809/wwlb3843
|View full text |Cite
|
Sign up to set email alerts
|

A Technologically Based Approach to Providing Quality Feedback to Students: A Paradigm Shift for the 21st Century

Abstract: This article will begin with a focus on the importance of providing quality feedback. Faculty providingconstructive and detailed feedback serves as an important component for effective student learningand is beneficial towards student achievement (Debuse, Lawley, & Shibl, 2007; Higgins, Hartley, &Skelton, 2002). According to Wolsey (2008), the desired outcome of feedback is to providecommunication between instructor and student, which promotes learning. Quality feedback is definedas providing students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This finding had been supported by [11] who found that timely feedback not only improved the student's learning process but also give positive emotion to student. In addition, [12] emphasized the vital role of quality feedback, claiming that systematic and constructive feedback would lead to producing an effective learning environment that yields positive outcomes on students' grades.…”
Section: Methodsmentioning
confidence: 99%
“…This finding had been supported by [11] who found that timely feedback not only improved the student's learning process but also give positive emotion to student. In addition, [12] emphasized the vital role of quality feedback, claiming that systematic and constructive feedback would lead to producing an effective learning environment that yields positive outcomes on students' grades.…”
Section: Methodsmentioning
confidence: 99%